2004
DOI: 10.1111/j.1834-7819.2004.tb00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing primary health clinical teams for public oral health services in Tasmania

Abstract: This paper reviews the problem of socio-economic health inequalities and highlights the relevance of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…This led to suggestions for the integration of oral health and the use of allied personnel or ancillary staff in the PHC system especially since oral health education does not require highly skilled personnel. This agrees with suggestions made by various researchers 9,12,14-29 on the use of less intensely trained personnel. Many opportunities exist for the members of the PHC team and voluntary workers to give advice on oral care 30 …”
Section: Discussionsupporting
confidence: 93%
“…This led to suggestions for the integration of oral health and the use of allied personnel or ancillary staff in the PHC system especially since oral health education does not require highly skilled personnel. This agrees with suggestions made by various researchers 9,12,14-29 on the use of less intensely trained personnel. Many opportunities exist for the members of the PHC team and voluntary workers to give advice on oral care 30 …”
Section: Discussionsupporting
confidence: 93%
“…In particular, the current model of oral health service that focuses on treatment with user payment, cost recovery, private insurance and public-private partnerships means the market organisation drives patient selection (Grytten and Golst 2013). This, in turn, limits elderly people's access to services in RACFs, especially those from lower socioeconomic groups, those living in rural/ remote areas, or those who are mentally or physically frail (Cane and Butler 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one study has shown that the delegation of basic community oral health services such as dental education or emergency care to other health professionals in the CHCs can help dentists and dental nurses improve the program . 28 However, this delegation should be supervised by a dental professional in order to maintain quality. Regulation that forbids all clinical services outside formal health facilities is also unfavorable in terms of optimizing resources.…”
Section: Discussionmentioning
confidence: 99%